Comparative evaluation of antibacterial effect and compressive strength of resin-modified glass-ionomer containing different antibiotics - Abdolrahim Davari; Hengameh Zandi; Farnaz Faraahat; Zahra Haddadi (Tehran University of Medical Sciences, 2021)
Background and Aims: Nowadays, new techniques are used to control dental caries that have the ability to kill cariogenic bacteria. Recently, the addition of antibiotics to glass ionomers has been proposed to reduce the overall number of saliva bacteria. The aim of this study was to compare the antimicrobial effect and compressive strength of resin- modified glass ionomer (RMGI) containing different antibiotics on Streptococcus mutans. Materials and Methods: A total of 120 specimens were prepared in 3 groups (n=40) including RMGI containing doxycycline with a concentration of 1.5%, RMGI containing a combination of ciprofloxacin, metronidazole and minocycline with a concentration of 1.5%, and RMGI without antibiotics as control group. To measure the antibacterial effect, the disk diffusion method and counting of Streptococcus mutans bacterial colonies were used and then the compressive strength test was performed. Data were collected into SPSS25 and analyzed by ANOVA and Kruskal-Wallis tests and the significance level was considered α=0.05. Results: The mean number of bacterial colonies in the RMGI group containing doxycycline in all three time intervals 1, 24 hours and 7 days was significantly lower than the specimens in the RMGI group containing the triple antibiotic (P<0.001). The mean compressive strength of the two experimental groups was lower than the control group but was not statistically significant (P=0.326). Conclusion: The addition of antibiotics at a concentration of 1.5% to RMGI resulted in a favorable antibacterial property with no significantly change in the compressive strength.